THE ROLE OF CORPORATE GOVERNANCE IN MODERATING THE RELATIONSHIP BETWEEN FINANCIAL PERFORMANCE RATIOS AND DISCLOSURE OF SUSTAINABILITY REPORTING TO STOCK PRICES - Nurholis; Nofryanti; Firman Tatariyanto (International Journal of Accounting, Management, Economics and Social Sciences (IJAMESC), 2025)
This study aims to examine the role of corporate governance in moderating the relationship between financial performance ratios and sustainability reporting disclosure on stock prices. The research uses a sample of all companies listed on the Indonesia Stock Exchange (IDX) during the 2022–2023 period. The sample was selected using the purposive sampling method, resulting in 98 out of 945 companies being analyzed. Hypothesis testing was conducted using Panel Data Regression Analysis and Moderated Regression Analysis (MRA) with the assistance of E-views software. The results indicate that Net Profit Margin (NPM) has a positive effect on stock prices. Current Ratio (CR) and Sustainability Reporting (SR) have no significant effect on stock prices. Corporate Governance (CG) does not moderate the relationship between Current Ratio, Net Profit Margin, and Sustainability Reporting on stock prices.